Perancangan Sistem Informasi Pemesanan Bouquet Berbasis Website Pada Dapur Kreatif di Kota Jambi - Ermawati, Emma; Metra, Pol; Triadi, Albet (Universitas Pahlawan Tuanku Tambusai, 2025)
This research is motivated by issues in the bouquet ordering process at Dapur Kreatif Florist, Kota Jambi, which is still conducted semi-digitally, leading to frequent recording errors and delayed confirmations. Therefore, this study aims to design a web-based bouquet ordering information system to improve order efficiency through features such as product management, shopping cart, checkout, and order tracking. The system development follows the Rapid Application Development (RAD) methodology using the Laravel framework and MySQL database. Software testing using Blackbox Testing indicates that the system functions properly, and an evaluation using the Likert scale, involving both the owner and customers, resulted in a feasibility score of 85% (highly feasible). This demonstrates that the system has been successfully designed according to the intended specifications and effectively meets user needs.